"Glycolipid biosurfactant-silica nanoparticles" based green application for enhancement of oil recovery. (12th May 2022) - Joshi, Sanket J.; Al-Farsi, Huda; Al-Bahry, Saif; Al-Wahaibi, Yahya
Abstract: Crude oil is still a major energy source, and it will continue to play a major role for several years to come. However, the industry is facing the challenge to cope the ever increasing demand and complexities on the recovery front in sustainable manner. To fulfill the continuous increase in demand, several enhanced oil recovery (EOR) techniques are in place to recover additional oil from depleting reservoirs. Among those possible technologies, biosurfactants and nanoparticles could possibly perform in a better and environmentally friendly manner. Here we show the possible EOR applications of glycolipids biosurfactants, either alone or in combinations with different concentrations of silica nanoparticles. Biosurfactants and nanoparticles were compatible, and it reduced both surface tension and interfacial tension values in the range of 26–28 mN/m, and 2.56–3.67 mN/m, respectively. Silica nanoparticles and glycolipid biosurfactants showed ∼10–30% additional oil recovery (AOR) from Berea sandstone core plugs, when tested individually at reservoir conditions. We observed ∼20–25% AOR using silica nanoparticles in combination with sophorolipids or rhamnolipids, where "NP + rhamnolipids" (40 ppm + 500 ppm, respectively) outperformed other combinations. To the best of our knowledge it is the first report for such combination to be used for environmentally friendly EOR applications.